Backward Cherenkov radiation emitted by polariton solitons in a microcavity wire. Issue 1 (December 2017) - Skryabin, D.; Kartashov, Y.; Egorov, O.; Sich, M.; Chana, J.; Rodriguez, L.; Walker, P.; Clarke, E.; Royall, B.; Skolnick, M.; Krizhanovskii, D.
Abstract Exciton-polaritons in semiconductor microcavities form a highly nonlinear platform to study a variety of effects interfacing optical, condensed matter, quantum and statistical physics. We show that the complex polariton patterns generated by picosecond pulses in microcavity wire waveguides can be understood as the Cherenkov radiation emitted by bright polariton solitons, which is enabled by the unique microcavity polariton dispersion, which has momentum intervals with positive and negative group velocities. Unlike in optical fibres and semiconductor waveguides, we observe that the microcavity wire Cherenkov radiation is predominantly emitted with negative group velocity and therefore propagates backwards relative to the propagation direction of the emitting soliton. We have developed a theory of the microcavity wire polariton solitons and of their Cherenkov radiation and conducted a series of experiments, where we have measured polariton-soliton pulse compression, pulse breaking and emission of the backward Cherenkov radiation. Cherenkov radiation is generated from fast electrons and its optical analogue plays an important role in many nonlinear optical effects. Here, Skryabin et al. demonstrate backward-propagating photonic Cherenkov radiation generated from solitons in a semiconductor exciton-polariton system.